PROSES PEMBUATAN STEP SHAFT PADA MIXER VERTICAL - Rachmat, Asep; Qori, Muhammad Qori Alfaruq (Universitas Majalengka, 2022)
Mixing Material (Mixing) is done in the world and everyday life. One of the many used equipment is a vertical shaft mixer (Vertical Stirred Mixer). Mixed materials are generally relatively thick liquid. Other materials processed are microbial fermentation, sand, medicinal material and granular powder. The process of mixing materials in the vertical shaft mixer is a major operating unit that is carried out for the process of chemical products, drugs, paint and paper processing, food processing and water management and activities in mining. The process of making a vertical axle using a conventional lathe. By using SS 304 steel material with a diameter of 80 mm and a length of 280 mm. Then the material underwent the surface leveling process, then continued with a multilevel flat flattery to finishing. Then proceed with the cutting process using the Frais machine and the process of turning the matrix. Keywords : Vertical Graded Shaft, Conventional Lathe, Axle